Certified Diabetes Educator: An Important Aid in Improving Patient Care in Diabetes - Joshi, Ameya; Shaikh, R. D. Sana N. (Journal of Social Health and Diabetes, 2019)
Diabetes mellitus is a chronic disease in which education plays a vital part. However, in India that is overburdened with diabetes has short of diabetes educators. Care for diabetes is limited by the adverse physician-to-patient ratio and lack of trained paramedical personnel. The following review focuses on role of diabetes educators in diabetes care and their current status in India.
Keywords: diabetes education; certification; National Diabetes Education Program